2019
DOI: 10.1088/1742-6596/1285/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation on lipid peroxidation, survival and growth of turmeric in vitro culture

Abstract: Gamma radiation has been widely applied in agriculture for crop improvement; however, it can induce oxidative stress in plant cell. This research aims to study effects of acute and chronic gamma irradiation on lipid peroxidation, plantlets survival and growth rate in M1V1 generation of turmeric. Plantlets cultured on MS medium were exposed to acute gamma radiation from Cs-137 (dose rate 3.7 Gy/min) at 0, 20, 40, 60 and 80 Gy. For chronic irradiation with a Co-60 source (dose rate 0.0057 Gy/min), turmeric were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Remarkable increases in proline and glycine betaine accumulation after gamma irradiation in the present study agree with previous reports of gamma radiation on Euryale ferox (Kumar et al . 2019) and turmeric plants (Chusreeaeom & Khamsuk 2019). Several reports have demonstrated that C .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkable increases in proline and glycine betaine accumulation after gamma irradiation in the present study agree with previous reports of gamma radiation on Euryale ferox (Kumar et al . 2019) and turmeric plants (Chusreeaeom & Khamsuk 2019). Several reports have demonstrated that C .…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, application of C. album extract accompanied by gamma radiation reduced lipid peroxidation in shoots of sunflower after 2 and 4 weeks compared to non‐treated control plants. Various reports have established that gamma radiation can decrease lipid peroxidation in turmeric plants (Chusreeaeom & Khamsuk 2019) and rice (Kim et al . 2012).…”
Section: Discussionmentioning
confidence: 99%